Ivermectin reduces in vivo coronavirus infection in a mouse experimental model - Arevalo, A. P. (2021)
SARS-CoV2 is a single strand RNA virus member of the type 2 coronavirus family, responsible for causing COVID-19 disease in humans. The objective of this study was to test the ivermectin drug in a murine model of coronavirus infection using a type 2 family RNA coronavirus similar to SARS-CoV2, the mouse hepatitis virus (MHV). BALB/cJ female mice were infected with 6,000 PFU of MHV-A59 (Group Infected; n=20) and immediately treated with one single dose of 500 μg/kg of ivermectin (Group Infected + IVM; n=20), or were not infected and treated with PBS (Control group; n=16). Five days after infection/treatment, mice were euthanized to obtain different tissues to check general health status and infection levels. Overall results demonstrated that viral infection induces the typical MHV disease in infected animals, with livers showing severe hepatocellular necrosis surrounded by a severe lymphoplasmacytic inflammatory infiltration associated with a high hepatic viral load (52,158 AU), while ivermectin administration showed a better health status with lower viral load (23,192 AU; p<0.05) and few livers with histopathological damage (p<0.05), not showing statistical differences with control mice (P=NS). Furthermore, serum transaminase levels (aspartate aminotransferase and alanine aminotransferase) were significantly lower in treated mice compared to infected animals. In conclusion, ivermectin seems to be effective to diminish MHV viral load and disease in mice, being a useful model for further understanding new therapies against coronavirus diseases.